Antibody Responses Against Plasmodium vivax TRAP Recombinant and Synthetic Antigens in Naturally Exposed Individuals From the Brazilian Amazon - Matos, Ada da Silva; Rodrigues-da-Silva, Rodrigo Nunes; Soares, Isabela Ferreira; Baptista, Barbara de Oliveira; Souza, Rodrigo Medeiros de; Bitencourt-Chaves, Lana; Totino, Paulo Renato Rivas; Sánchez-Arcila, Juan Camilo; Daniel-Ribeiro, Cláudio Tadeu; López-Camacho, César; Reyes-Sandoval, Arturo; Pratt-Riccio, Lilian Rose; et al. (Frontiers in Immunology, 2019)
Thrombospondin-related adhesive protein (TRAP) of malaria parasites is essential for sporozoite motility and invasion into mosquito's salivary gland and vertebrate's hepatocyte and is, thus, considered a promising pre-erythrocytic vaccine candidate. Despite the existence of few reports on naturally acquired immune response against Plasmodium vivax TRAP (PvTRAP), never explored so far in the Amazon region, results are conflicting. Here, we characterized the (IgG and IgG subclass) antibody reactivity against recombinant PvTRAP in a cross-sectional study of 299 individuals naturally exposed to malaria infection in three municipalities (Cruzeiro do Sul, Mâncio Lima and Guajará) from the Acre state of the Brazilian Amazon. In addition, the full PvTRAP sequence was screened for B-cell epitopes using in silico and in vitro approaches. Firstly, we confirmed that PvTRAP is naturally immunogenic in the cohort population since 49% of the individuals were IgG-responders to it. The observed immune responses were mainly driven by cytophilic IgG1 over all other sublcasses and the IgG levels that was corelated with age and time of residence in the studied area (p<0.05). Interestingly, only the levels of specific anti-TRAP IgG3 seemed to be associated with protection, as IgG3 responders presented a significantly higher time elapse since the last malaria episode than those recorded for IgG3 non-responders. Regarding the B-cell epitope mapping, among the 148 responders to PvTRAP, four predicted epitopes were confirmed by recognition of antibodies (PvTRAPR197-H227; PvTRAPE237-T258; PvTRAPP344-G374 and PvTRAPE439-K454). Nevertheless, the frequency of responders against these peptides were low and did not show a clear correlation with the antibody response against the corresponding antigen. Moreover, none of the linear confirmed epitopes were located in the binding regions of PvTRAP in respect to the host cell ligand. Collectively, our data confirm the PvTRAP immunogenicity among Amazon inhabitants, while suggesting that the main important B-cell epitopes are not linear.